The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1093/brain/awn167
|View full text |Cite
|
Sign up to set email alerts
|

Enuresis as a premorbid developmental marker of schizophrenia

Abstract: SUMMARY There is comparatively little information about premorbid maturational brain abnormalities in schizophrenia. We investigated whether a history of childhood enuresis, a well-established marker of neurodevelopmental delay, is associated with schizophrenia and with measures of brain abnormalities also associated with schizophrenia. A DSM-IV based history of enuresis, volumetric brain MRI scans, and neuropsychological testing were obtained in patients with schizophrenia, their non-psychotic siblings, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 61 publications
(67 reference statements)
1
15
0
Order By: Relevance
“…Hyde et al [16] found that adult patients with schizophrenia (SCZ) have an increased rate of childhood enuresis (21%) compared with their healthy siblings (11%) or with normal control patients (7%). This is the first, and thus far largest, study of childhood enuresis in adult patients with SCZ to date, and is the only study of adults with a history of enuresis examined with both neuropsychological testing and structural brain imaging.…”
Section: A Childhood Problem Continues Into Adulthoodmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyde et al [16] found that adult patients with schizophrenia (SCZ) have an increased rate of childhood enuresis (21%) compared with their healthy siblings (11%) or with normal control patients (7%). This is the first, and thus far largest, study of childhood enuresis in adult patients with SCZ to date, and is the only study of adults with a history of enuresis examined with both neuropsychological testing and structural brain imaging.…”
Section: A Childhood Problem Continues Into Adulthoodmentioning
confidence: 99%
“…Hyde et al [16] found that enuresis potentially is heritable: the familial risk of enuresis was 2.6 times greater in siblings of enuretic probands than in siblings of nonenuretic probands. Moreover, they found that at least healthy female siblings of patients with SCZ have a significantly increased frequency of enuresis, suggesting that enuresis may be related to genetic risk factors for SCZ.…”
Section: A Childhood Problem Continues Into Adulthoodmentioning
confidence: 99%
“…Areas of the brain such as the insula, the anterior cingulate cortex, and the prefrontal cortex are responsible for bladder control and monitoring 9 and have been implicated in ADHD and LUTD. 8 Hyde et al 10 considered enuresis during childhood a premorbid developmental marker of schizophrenia. In a group of patients with schizophrenia, 21% had enuresis during childhood versus 11% of their siblings and 7% of healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…These abnormalities were located in the thalamus, frontal lobe, anterior cingulate cortex and insula [101]. Adults patients with schizophrenia who had NE in their childhood were found to have significant reduction in the brain gray matter involving the frontal and parietal lobes [102]. Further evidences were derived from neurophysiological studies [103][104][105].…”
Section: Brain Maturation and Nocturnal Enuresis In Scamentioning
confidence: 99%